Comparative Study of Data Synchronization Techniques for Mobile Applications in Network-Constrained Environments - Baz Mohammad Nazari; Mohammad Sohaib Saqib; Rohullah Aimaq (Gameology and Multimedia Expert, 2026)
The rapid growth of mobile applications across finance, education, healthcare, and social services depends on data synchronization: the process of keeping information shared between a mobile device and a central server consistent, accurate, and current. For millions of users in developing countries such as Afghanistan, where internet connectivity is frequently weak, unstable, or unavailable, synchronization failures are a daily frustration rather than a rare exception. This study conducts a systematic comparative review of data synchronization techniques for mobile applications operating under challenging network conditions, following the guidelines of Kitchenham and Charters. A structured search of IEEE Xplore, ACM Digital Library, SpringerLink, ScienceDirect, and Google Scholar (2010-2026) produced 45 eligible studies after screening and quality appraisal. Four primary synchronization categories were identified and compared across speed, resource consumption, security, stability, and implementation complexity: real-time (push-based), offline-first, API-based (pull-based), and cloud-based synchronization. Real-time synchronization offers the lowest latency under ideal connectivity but degrades sharply when connections drop; offline-first synchronization sustains full read-write functionality during disconnection, at the cost of higher implementation complexity and local storage use; API-based pull synchronization is simplest to implement but loses ground under frequent polling; and cloud-based platforms accelerate development but introduce vendor lock-in and scaling costs. Under low-bandwidth and intermittent connectivity, offline-first architecture consistently ranked first across the reviewed evidence. The study concludes that offline-first design should be the default synchronization strategy for mobile applications targeting network-constrained environments such as Afghanistan, supplemented selectively by real-time or cloud-based components where connectivity allows.